This Is Our School! : Race and Community Resistance to School Reform - Gordon, Hava Rachel, 1974- (Book collections on Project MUSE., 2021)
"The book provides a rich description of four movement sectors in one city all claiming to fight for educational justice. It combines theoretical insight from studies of urban reform, neoliberalism, education and social movements, and integrates rich ethnographic detail and activist narratives to illustrate education movement victories and defeats"--